PENGARUH BUDAYA BISNIS MASYARAKAT ,LITERAIS KEUANGAN, SELF EFFICACY DAN LINGKUNGA KELUARGA TERHADAP MINAT BERWIRAHUSAHA DI KOTA YOGYAKARTA - Srilestari Grensi Woli; Dewi Kusuma Wardani (Jurnal Akuntansi, 2021)
This study aims to examine the positive influence of community business culture on the interest in community entrepreneurship in Yogyakarta City; to test the positive influence of finance on the interest in entrepreneurship in the city of Yogyakarta; to test the positive effect of self efficacy on the interest in entrepreneurship in the city of Yogyakarta; and to test the positive influence of the family environment on the entrepreneurial interest in the community in Yogyakarta City. This type of research is quantitative research, namely empirical research where the data is in the form of numbers or something that can be calculated. When viewed from the research objectives, this research includes causal associative research, which is research that aims to see the influence between one variable and another. The sample taken in this study is the entrepreneurial community in the city of Yogyakarta with a total of 97 people. Data analysis using multiple linear regression analysis. The results showed that culture has a positive effect on the interest in entrepreneurship in the city of Yogyakarta; Financial literacy has a positive effect on people's interest in entrepreneurship in Yogyakarta City; self-efficacy has a positive effect on the interest in entrepreneurship in the city of Yogyakarta; and the family environment has a positive effect on the interest in entrepreneurship in the city of Yogyakarta.